THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.
Publisher: Zenodo

Teacher Burnout: Applying the Job Demands and Resources Model in Macao - Ng, Kun Keong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Rewriting Life Story and Career Development: a Case Study Using a Narrative Approach - Choi, Ka Lok (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Parents views on special education in Macao - Wong, Man Wa (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Leisure time and well being of elderly in Macau - Dias, Anabela Maria (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Interpreting the causes of depression in Macau elderly - Kwok, Wing Yee (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Family constellations: a systematic review and a critical analysis - Kuan, Man Sok (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effects of family closeness and conflict on young adults' peer relationships - Chan, Mei Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Effectiveness of Art Therapy for Children with Special Educational Needs - Ho, Weng Chong (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Children's with SEN Views About Their Experience in Inclusive Education - Lai, Hoi Lam (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Adolescent pathways to hikikomori in Macau - Hon, Leng Ian (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A vignette: study do casual explanation and continuum beliefs affect Macau college students' attitudes towards mental disorders? - Wong, Ka In (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph